SOCIO-HISTORICAL FACTORS OF LAW PERCEPTION IN “LIVING LAW” CONCEPT BY EUGEN EHRLICH - KARVATSKA, S. (Ehrlich’s Journal, 2023)
Using the systemic approach to the knowledge of law, socio-historical factors of law perception were defined in the concept of “living law” by Eugen Ehrlich. It was established that the features of the historical-social context of cognition of law are connected, first of all, with the features of the object of this knowledge, which in general terms can be defined as the law in history, or historical-legal reality. It was substantiated that according to Ehrlich’s concept, law is a social phenomenon that takes place and functions in society; and on the other hand, law is a phenomenon that exists in the time dimension. It was proved that Eugen Ehrlich disagreed with the assertions of historians that the scientific understanding of law can only be disclosed in the context of history. This is a scientific truth, as the scientist stated, without practical value. It is noted that Ehrlich criticized the historians for the analysis of legal norms, stating that, since for the law historians of all times the law was not legal relations, but only legal norms, so they left out the real legal relations (“living law”). Historians of law, according to Ehrlich, failed to combine different methods and principles of scientific perception of law, and, as a result, they couldn’t define the scientific character criteria as a whole. Therefore, for the full disclosure of the nature of law, for the formulation of law cognition methods, Ehrlich defined the basic postulate: the legal science should be not only historical, but also sociological.